'Cochlear-type' hearing loss as part of aquaporin-4 neuromyelitis optica spectrum disorder. Issue 1 (11th January 2021) - Shaw, Benjamin; Raghavan, Ramasamy Srinivasa; Warner, Graham; Palace, Jacqueline
Abstract : Neuromyelitis optica spectrum disorder is an inflammatory autoimmune central nervous system condition caused in the majority of cases by aquaporin-4 IgG antibodies. Aquaporin-4 is expressed in the cochlear and vestibular nuclei regions in the brainstem and a handful of cases of retro-cochlear type hearing loss have been documented in the literature. Aquaporin-4 has also been reported within the organ of Corti and the cristae and maculae of the vestibular apparatus. We present a case where there is evidence of peripheral (labyrinthine) rather than central pathology and propose this is due to autoimmune inflammation as part of neuromyelitis optica spectrum disorder. This is the first case in the literature suggesting a 'cochlear-type' hearing loss occurring as part of neuromyelitis optica spectrum disorder. It raises the possibility of peripheral relapses of neuromyelitis optica spectrum disorder going unnoticed, resulting in patient morbidity, and highlights the importance of research within this area.